“Redes Sociales en el rendimiento académico de los estudiantes de Octavo, Noveno y Décimo año de Educación General Básica de la unidad educativa ‘‘Nuestro Mundo Eco-Rio’’ .Riobamba. Chimborazo. período 2016-2017” - Choto Guallán, Jorge Aníbal (2017)
This research was conducted with the purpose of establishing the relationship of social networks with academic performance, as well as, what are social networks?, What is the academic performance of students? And how do social networks relate to academic performance? Social networks in this century have revolutionized society not only in the institution under investigation, but also at the national and global levels, especially among young people and adolescents. For this purpose, we applied surveys and comparison cards to 50 student´s, the questionnaire consists of 10 questions in which it questions the time they use and the interference in the educational activities caused by being immersed in social networks. It also provides a comparison of current grades or mark obtained by the students in two periods in two periods, carried out by a presentation, analysis and interpretation of data obtained. This research will be done to evidence if social networks are correlated with a student´s academic performance. Prior to the observation of low academic performance, we assume the lack of attention to class due to the dominance which social network have now. Consequently, it is necessary to analyze if de stated question is true, and in turn seek a preventive action for adolescents who are not yet immersed; and be educated or informed in the proper use of social networks and schedules that do not hinder the responsibilities they have as students.